THE ANALYSIS OF TRANSFORMASTIONAL AND TRANSACTIONAL LEADERSHIP STYLE’S INFLUENCE TO JOB SATISFACTION AND IT’S INFLUENCE TO EMPLOYEE PERFORMANCE AT NGO SAMPAN KALIMANTAN - B2043131011, RIZANI RAMADHAN (Universitas Tanjungpura, 2019)
The main issue of this research is the influence of transformational and transactional leadership style in improving job satisfaction and employee performance. The purpose of this study is to analyze the influence of transformational and transactional leadership styles in Sampan Kalimantan NGO. This research is a causality research that aims to prove the cause from the variables studied. The sampling design used in this research is the saturated sampling technique (census), which is the sampling technique when all members of the population are used as a sample that is all employees of Sampan Kalimantan NGO (excluding leaders) amounted to 59 people. Data obtained from questionnaires collected and analyzed with quantitative analysis using SEM (Structural Equation Modeling) model with the help of Warp PLS 6.0 program. The results show that (1) transformational leadership has a positive and significant influence on employee job satisfaction, (2) transactional leadership has a positive but not significant influence on job satisfaction, (3) transformational leadership has positive and significant influence on employee performance, (4) ) Transactional leadership has a positive but not significant influence on employee performance, and (5) job satisfaction has a positive and significant influence on employee performance.. Keywords : Transactional Leadership, Transformational Leadership, Job Satisfaction, Employee’s Performance